2010
DOI: 10.1002/hlca.201000126
|View full text |Cite
|
Sign up to set email alerts
|

Withanolides from Aureliana fasciculata var. fasciculata

Abstract: In the first phytochemical study of the Aureliana genus (Solanaceae), two new withanolides, 1 and 2, together with two known sterols, were isolated from the MeOH extract of the leaves of Aureliana fasciculata var. fasciculata. The structures were established as (4S,22R)-16a-acetoxy-5b,6b-epoxy-4b,17a-dihydroxy-1-oxowitha-2,24-dienolide (aurelianolide A) and (4S,22R)-16a-acetoxy-4b,17a-dihydroxy-1-oxowitha-2,5,24-trienolide (aurelianolide B). The new compounds possessed the unusual 16a,17a-dioxygenated group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Over the last 46 years, approximately 750 withanolides, exhibiting more than 22 carbon skeletons (Figure 2), have been reported from various plant sources. As listed in Table 1, withanolides are predominant in 25 genera (including Acnistus , Datura , Deprea , Discopodium , Dunalia , Iochroma, Jaborosa , Lycium , Nicandra , Physalis , Solanum , Trechonaetes , Tubocapsicum , Vassobia , Withania and Witheringia ) of the Solanaceae family [27, 1012]. Not limited to the Solanaceae, withanolides have also been isolated from a smaller number of species in the Dioscoreaceae [13], Fabaceae [7], Lamiaceae [2], Myrtaceae [14], Taccaceae [2], and from two genera in the marine Alcyoniidae [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 46 years, approximately 750 withanolides, exhibiting more than 22 carbon skeletons (Figure 2), have been reported from various plant sources. As listed in Table 1, withanolides are predominant in 25 genera (including Acnistus , Datura , Deprea , Discopodium , Dunalia , Iochroma, Jaborosa , Lycium , Nicandra , Physalis , Solanum , Trechonaetes , Tubocapsicum , Vassobia , Withania and Witheringia ) of the Solanaceae family [27, 1012]. Not limited to the Solanaceae, withanolides have also been isolated from a smaller number of species in the Dioscoreaceae [13], Fabaceae [7], Lamiaceae [2], Myrtaceae [14], Taccaceae [2], and from two genera in the marine Alcyoniidae [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…2), have been reported from various plant sources. As listed in Table 1, withanolides are predominant in 25 genera (including Acnistus, Datura, Deprea, Discopodium, Dunalia, Iochroma, Jaborosa, Lycium, Nicandra, Physalis, Solanum, Trechonaetes, Tubocapsicum, Vassobia, Withania, and Witheringia) of the Solanaceae family [2][3][4][5][6][7][10][11][12]. Not limited to the Solanaceae, withanolides have also been isolated from a smaller number of species in the Dioscoreaceae [13], Fabaceae [7], Lamiaceae [2], Myrtaceae [14], Taccaceae [2], and from two genera in the marine Alcyoniidae [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[8] This chemotaxonomic information is in agreement with previous phytochemical studies of the genus Aurealina, which reported the isolation of withanolides. [7] Similarly, here we describe the structural elucidation of athenolides in the genus Athenaea. Therefore, in this study, the phytochemical study of A. martiana supported its positon in the subfamily Solanoideae as well as the chemical relationships between the Athenaea and Aureliana genera by the occurrence of steroidal lactones.…”
Section: Chemotaxonomic Considerationsmentioning
confidence: 97%
“…[2] [3] The taxonomic knowledge of the Athenaea genus has been the subject of several reviews, [4 -6] and recently botanical studies suggested the re-evaluation of the generic status of this genus as a synonym of Aureliana. [1] [3] Previous phytochemical investigations of species of the genus Aureliana led to identification of withanolides, [7] whereas there are no studies of Athenaea species. Withanolides are a class of naturally occurring C(28) steroidal lactones structurally based on the ergostane-type skeleton, and recognized as chemotaxonomy markers of Solanaceae.…”
Section: Introductionmentioning
confidence: 99%